Matrix effects and calibration limitations in ion probe U-Pb and Th-Pb dating of monazite - Fletcher, Ian; McNaughton, Neal; Davis, W.; Rasmussen, Birger (Elsevier Science BV, 2010)
Monazite can be used for U-Pb and Th-Pb dating of awide variety of rocks and geological processes, particularly metamorphism. In many instances ion microprobe analysis is the preferred method for dating monazite, combining good analytical precision with m-scale spatial resolution. However, ion microprobe dates can be compromised by matrix effects on the ionisation efficiencies of different secondary ionic species, which can bias monazite Pb+/ThOn + and Pb+/UOn + data by as much as ~40% and ~30%, respectively, for known monazite compositions. These effects appear to be entirely attributable to the sputtering process, in which case similar effects exist in data from all ion probes. The effects on data ratios are modified, sometimes exacerbated or reversed, when data are subjected to the correlation-based Pb/Th and Pb/U calibrations that are now commonly used. One-dimensional calibrations of 206Pb+/270[UO2]+ and 208Pb+/264[ThO2]+ are recommended. Corrections derived from data for a suite of reference materials with diverse compositions can reduce biases in 208Pb/232Thages to <~2% and in 206Pb/238U ages to <~1%. The matrix effects come predominantly from variations in the concentrations of Th, U, Pb, light rare earth elements (LREE) and Y. La/Ce is an effective proxy for REE composition in many monazites, but for some monazites it would also be necessary to monitor Nd. Matrix corrections can be applied without measuring all LREE, using ion probe data alone. Other interacting data complications, such as Pb/Pb fractionation and an isobar at 204Pb+, can be addressed without iterative data reduction.